TEK YANLI YARIK DUDAK BURNU DEFORMİTESİNİN PRİMER ONARIMI - AYGIT, A. Cemal; GÜZEL, M. Zeki; ÇINAR, Can; YILDIRIM, Alpagan Mustafa (Cerrahpaşa Medical Journal, 2014)
Background. Despite the recent advances in plastic surgery, treatment of the cleft lip nasal deformity is still a great problem. We suggest a simplified procedure for reconstruction of the position and shape of the cleft side alar cartilage that cause deformity. Design. During the cleft lip repair by the Millard technique, the lower lateral cartilage dissected and fully mobilised from overlying tissue. It is repositioned anteriorly, superiorly and medially and stabilised in its new position by using throughand, through crosswise suture tied over tulle grasses. These stent sutures go through skin and nasal lining but over the septal caıtilage. Results. We treated the displaced, malaligned and deformed cartilage of the nose on 10 patients with unilateral in complete and complete cleft lip, using this simplified procedure. The results assessed functionally and aesthetically good. Conclusion. This simplified procedure eliminates the severe cleft nasal deformity seen in many secondary cases.